The emotional burden of caregiving for patients with cirrhosis - Zachary M. Saleh; Najat E. Salim; Samantha Nikirk; Marina Serper; Elliot B. Tapper (Hepatology Communications, 2022)
Abstract Caregivers for patients with cirrhosis face immense physical and psychological strain that negatively impact quality of life and ability to care for oneself. The aim is to explore the caregiver experience for patients with cirrhosis, identify prominent stressors, and understand the multidimensional contributors to caregiver burden, to help tailor effective interventions. The caregivers of 25 patients with decompensated cirrhosis underwent semistructured in‐person interviews and completed written exercises targeting emotional disclosure or resilience training that were analyzed for dominant emotions and themes. Burden was quantified using the Zarit Burden Interview‐12 (ZBI, range 0–48), Distress Thermometer (0–10), and Caregiver Captivity Index (0–4). Quality of life was assessed with a visual analog scale (0–100). Median ZBI was moderate (14 [10–19]), as was distress (5 [2–7]), and captivity (2 [1–4]). Quality of life was fair (80 [70–85]). Dominant emotions included anxiety, guilt, fear, frustration, captivity, and resentment. Prominent themes included lack of time for self‐care, hierarchy of caregiver role, support from versus frustration with medical professionals, social support, spirituality and religion, and disease‐related restrictions. Hepatic encephalopathy, and need to follow strict nutrition and diet recommendations, are frequent sources of disease‐related caregiver burden. The health care system confers some degree of burden, especially when doubts arise regarding physician competence. Conclusion: Caregiver burden is significant. The impact of interventions to alleviate caregiver burden should be explored, so that their appreciated efforts do not have such detrimental effects on their quality of life.